Comparative Study of Different CO2 Injection Modes for Baronia RV2 Reservoir - Siti Fatimah binti Mazalan, Siti Fatimah (Universiti Teknologi Petronas, 2008)
This project presents an experimental study of comparing different CO2 injection mode for Baronia RV2 reservoir. It is the main objective to determine the most optimum CO2 injection mode for this field. Using a coreflood equipment, CO2 displacements were conducted on four core plugs saturated with Baronia RV2 crude oil.